Analysis of an airfoil using a transition and turbulence model - Islam, Mazharul; Fürst, Jiri; Wood, David H.; Ani, Farid Nasir (Trans Tech Publications Ltd, 2016)
In order to evaluate the performance of airfoils with computational fluid dynamics (CFD) tools, modelling of transitional region in the boundary layer is very critical. Currently, there are several classes of transition-based turbulence model which are based on different methods. Among these, the k-kL- ω, which is a three equation turbulence model, is one of the prominent ones which is based on the concept of laminar kinetic energy. This model is phenomenological and has several advantageous features. Over the years, different researchers have attempted to modify the original version which was proposed by Walter and Cokljat in 2008 to enrich the modelling capability. In this article, a modified form of k-kL-ω transitional turbulence model has been used with the help of OpenFOAM for an investigative CFD analysis of a NACA 4-digit airfoil at range of angles of attack.